Determinants of Shariah Governance Disclosure in Islamic Banks: Evidence from Indonesia and Malaysia - Sandy, Andre Kurniawan; Filianti, Dian (Jurnal Ekonomi Syariah Teori dan Terapan, 2025)
This study aims to determine the influence of company age, company size, third-party funds growth, and institutional ownership on the disclosure of sharia governance, measured using the content analysis method, in Islamic banks in Indonesia and Malaysia both partially and simultaneously. The population used in this study is Islamic banks in Indonesia and Malaysia during the 2019-2023 period. The sampling technique used is purposive sampling, resulting in 10 Islamic banks in Indonesia with 50 data points and 12 Islamic banks in Malaysia with 60 data points. This study employs a quantitative method with a panel data regression analysis model, using EViews 13 software. The results of this study found that, partially, the variable of company age has a significant positive effect on sharia governance disclosure, and the variable of company size has a significant negative effect on sharia governance disclosure in Islamic banks in Indonesia and Malaysia, while third-party funds growth and institutional ownership do not have a significant effect on sharia governance disclosure in Islamic banks in Indonesia and Malaysia. Simultaneously, the variables of company age, company size, third-party funds growth, and institutional ownership significantly influence the sharia governance disclosure of Islamic banks in Indonesia and Malaysia from 2019-2023.